Definition of K(trans) and FA Thresholds for Better Assessment of Experimental Glioma Using High-field MRI: A Feasibility Study - Engelhorn, Tobias; Schwarz, Martin; Heß, Andreas; Budinsky, Lubos; Pitann, Patrick; Eyüpoglu, Ilker Yasin; Dörfler, Arnd (Clinical Neuroradiology, 2014)
To define K(trans) and fractional anisotropy (FA) thresholds in correlation to histology for improved magnetic resonance imaging (MRI) tumor assessment in an animal model of brain glioma.Twelve rats underwent 4.7 T MRI at day 10 after tumor implantation. Anatomical scans (T2, T1 at 8 min after double dose contrast application) as well as dynamic contrast-enhanced (DCE) imaging with calculation of K(trans) and diffusion tensor imaging (DTI) with calculation of FA were performed. T2- and T1-derived tumor volumes were calculated and thresholds for K(trans) and FA were defined for best MRI tumor assessment correlated to histology.Tumor volumes were 159 ± 14 mm(3) (histology), 126 ± 26 mm(3) (T1 with contrast, r = 0.76), and 153 ± 12 mm(3) (T2, r = 0.84), respectively. K(trans)- and FA-derived tumor volumes were 160 ± 16 mm(3) (for K(trans) ³ 0.04 min(-1), r = 0.94), and 159 ± 14 mm(3) (for FA £ 0.14, r = 0.96), respectively.DCE-MRI and DTI with calculation of K(trans) and FA maps allow very precise brain glioma assessment comparable to histology if established thresholds for the given tumor model are used.
EVALuna2:8504

EFhd2/Swiprosin-1 is a common genetic determinator for sensation-seeking/low anxiety and alcohol addiction - Mielenz, Dirk; Reichel, Martin; Jia, T.; Quinlan, E. B.; Stöckl, Thomas; Mettang, M.; Zilske, Daniel; Kirmizi Alsan, Elif; Schoenberger, P.; Praetner, M.; Huber, Sabine; Amato, Davide; et al. (Molecular Psychiatry, 2017)
In many societies, the majority of adults regularly consume alcohol. However, only a small proportion develops alcohol addiction. Individuals at risk often show a high sensation-seeking/low-anxiety behavioural phenotype. Here we asked which role EF hand domain containing 2 (EFhd2; Swiprosin-1) plays in the control of alcohol addiction-associated behaviours. EFhd2 knockout (KO) mice drink more alcohol than controls and spontaneously escalate their consumption. This coincided with a sensation-seeking and low-anxiety phenotype. A reversal of the behavioural phenotype with β-carboline, an anxiogenic inverse benzodiazepine receptor agonist, normalized alcohol preference in EFhd2 KO mice, demonstrating an EFhd2-driven relationship between personality traits and alcohol preference. These findings were confirmed in a human sample where we observed a positive association of the EFhd2 single-nucleotide polymorphism rs112146896 with lifetime drinking and a negative association with anxiety in healthy adolescents. The lack of EFhd2 reduced extracellular dopamine levels in the brain, but enhanced responses to alcohol. In confirmation, gene expression analysis revealed reduced tyrosine hydroxylase expression and the regulation of genes involved in cortex development, Eomes and Pax6, in EFhd2 KO cortices. These findings were corroborated in Xenopus tadpoles by EFhd2 knockdown. Magnetic resonance imaging (MRI) in mice showed that a lack of EFhd2 reduces cortical volume in adults. Moreover, human MRI confirmed the negative association between lifetime alcohol drinking and superior frontal gyrus volume. We propose that EFhd2 is a conserved resilience factor against alcohol consumption and its escalation, working through Pax6/Eomes. Reduced EFhd2 function induces high-risk personality traits of sensation-seeking/low anxiety associated with enhanced alcohol consumption, which may be related to cortex function.
EVALuna2:4036

MIF-CD74 signaling impedes microglial M1 polarization and facilitates brain tumorigenesis - Ghoochani, Ali; Schwarz, Martin; Yakubov, Eduard; Engelhorn, Tobias; Dörfler, Arnd; Buchfelder, Michael; Bucala, R.; Savaskan, N. E.; Eyupoglu, I. Y. (Oncogene, 2016)
Microglial cells in the brain tumor microenvironment are associated with enhanced glioma malignancy. They persist in an immunosuppressive M2 state at the peritumoral site and promote the growth of gliomas. Here, we investigated the underlying factors contributing to the abolished immune surveillance. We show that brain tumors escape pro-inflammatory M1 conversion of microglia via CD74 activation through the secretion of the cytokine macrophage migration inhibitory factor (MIF), which results in a M2 shift of microglial cells. Interruption of this glioma-microglial interaction through an antibody-neutralizing approach or small interfering RNA (siRNA)-mediated inhibition prolongs survival time in glioma-implanted mice by reinstating the microglial pro-inflammatory M1 function. We show that MIF-CD74 signaling inhibits interferon (IFN)-γ secretion in microglia through phosphorylation of microglial ERK1/2 (extracellular signal-regulated protein kinases 1 and 2). The inhibition of MIF signaling or its receptor CD74 promotes IFN-γ release and amplifies tumor death either through pharmacological inhibition or through siRNA-mediated knockdown. The reinstated IFN-γ secretion leads both to direct inhibition of glioma growth as well as inducing a M2 to M1 shift in glioma-associated microglia. Our data reveal that interference with the MIF signaling pathway represents a viable therapeutic option for the restoration of IFN-γ-driven immune surveillance.
EVALuna2:33151

Multifocal electroretinography after high dose chloroquine therapy for malaria - de Carvalho, Aline Correa; Schwarz, Martin; Souza, Givago da Silva; Gomes, Bruno Duarte; Rosa, Alexandre Antônio Marques; da Silva Ventura, Ana Maria Revoredo; de Souza, José Maria; Silveira, Luiz Carlos de Lima; Kremers, Jan (Journal of Ophthalmic & Vision Research, 2013)
To investigate changes in multifocal electroretinography (mfERG) parameters associated with high dose chloroquine therapy for treatment of malaria in the Amazonia region of Brazil.Forty-eight subjects who had received chloroquine treatment for single or multiple malaria infections with a cumulative dose ranging from 1,050 to 27,000mg were included. The control group consisted of 37 healthy aged-matched subjects. Data was collected on amplitude and implicit time of the N1, P1 and N2 waves in the central macular hexagon (R1) and in five concentric rings at different retinal eccentricities (R2-R6).No significant difference was observed in any mfERG parameter between chloroquine treated patients and control subjects. A comparison with previous data obtained from patients with rheumatologic disorders in the same region of Brazil who had received larger cumulative doses of chloroquine and had displayed mfERG changes, indicated that retinal toxicity seems to be dependent on cumulative dose.Lack of mfERG changes in the current study suggests that intensive high dose chloroquine therapy for treatment of malaria is not associated with retinal toxicity.
EVALuna2:21145

Novel technique for high-precision stereotactic irradiation of mouse brains - Hartmann, Josefin; Wölfelschneider, Jens; Stache, Christina; Buslei, R.; Derer, Anja; Schwarz, Martin; Bäuerle, Tobias; Fietkau, Rainer; Gaipl, Udo; Bert, Christoph; Hoelsken, A.; Frey, Benjamin (Strahlentherapie und Onkologie, 2016)
Small animal irradiation systems were developed for preclinical evaluation of tumor therapy closely resembling the clinical situation. Mostly only clinical LINACs are available, so protocols for small animal partial body irradiation using a conventional clinical system are essential. This study defines a protocol for conformal brain tumor irradiations in mice.CT and MRI images were used to demarcate the target volume and organs at risk. Three 6 MV photon beams were planned for a total dose of 10 fractions of 1.8 Gy. The mouse position in a dedicated applicator was verified by an X-ray patient positioning system before each irradiation. Dosimetric verifications (using ionization chambers and films) were performed. Irradiation-induced DNA damage was analyzed to verify the treatment effects on the cellular level.The defined treatment protocol and the applied fractionation scheme were feasible. The in-house developed applicator was suitable for individual positioning at submillimeter accuracy of anesthetized mice during irradiation, altogether performed in less than 10 min. All mice tolerated the treatment well. Measured dose values perfectly matched the nominal values from treatment planning. Cellular response was restricted to the target volume.Clinical LINAC-based irradiations of mice offer the potential to treat orthotopic tumors conformably. Especially with respect to lateral penumbra, dedicated small animal irradiation systems exceed the clinical LINAC solution.
EVALuna2:7317